2015
DOI: 10.1002/ar.23120
|View full text |Cite
|
Sign up to set email alerts
|

Precocious Ossification of the Tympanoperiotic Bone in Fetal and Newborn Dolphins: An Evolutionary Adaptation to the Aquatic Environment?

Abstract: The present study, performed with a dual-energy X-ray (DXA) bone densitometer on a series of fetal and newborn striped and short-beaked common dolphins, shows that the bone density of the area of the tympanic bulla within the tympanoperiotic complex starts with 0.483 g cm 22 in 5-to 6-month-old specimens of striped (or common) dolphin fetuses and reaches 1.841 g cm 22 in newborn striped dolphins, with values consistently higher than in other parts of the skull or elsewhere in the skeleton. The same results app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The rationale for comparing the species that we mainly describe in our study, i.e., the bottlenose dolphin, with specimens of the striped dolphin, is based on their common origin in the family Delphinidae and on the similarity of their morphology (see also Table 2 ). Furthermore, their developmental stages are comparable, as showed in a recent study ( Cozzi et al, 2015 ) in which embryos and fetuses of Sc , Dd , and Tt were analyzed for progressive very early deposition of calcium salts in the tympanoperiotic complex (a rather distinctive trait of marine Cetartiodactyla). The bottlenose dolphin Tt is approx.…”
Section: Discussionsupporting
confidence: 52%
“…The rationale for comparing the species that we mainly describe in our study, i.e., the bottlenose dolphin, with specimens of the striped dolphin, is based on their common origin in the family Delphinidae and on the similarity of their morphology (see also Table 2 ). Furthermore, their developmental stages are comparable, as showed in a recent study ( Cozzi et al, 2015 ) in which embryos and fetuses of Sc , Dd , and Tt were analyzed for progressive very early deposition of calcium salts in the tympanoperiotic complex (a rather distinctive trait of marine Cetartiodactyla). The bottlenose dolphin Tt is approx.…”
Section: Discussionsupporting
confidence: 52%
“…[ 33 , 59 ] One might expect comparable ontogenetic change in the size and shape of bones and the skull in fossil cetaceans, with implications for cladistic coding and phylogenetic placement. In living odontocetes, the periotic ossifies early in fetal development [ 60 ], and generally shows little change in size or shape after birth [ 61 ]. Further, this single element is feature-laden [ 21 ], with many characters available for cladistic analysis and/or identification to species level [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Frainer et al () found that the sound generating structures and auditory sense of P. blainvillei might already be functional at birth. Thus, the observed trends suggest that the development of the external nares and the posterior portion of the premaxilla are common features among odontocetes, probably associated with the early development of breathing and sound production apparatuses, albeit they have a continuous postnatal maturation (Rauschmann et al, ; Cozzi et al, ).…”
Section: Discussionmentioning
confidence: 99%